Nitrogen catabolite repression in a glutamate auxotroph of Saccharomyces cerevisiae. - Kang, L (1982)
The biosynthesis of asparaginase II in Saccharomyces cerevisiae is subject to nitrogen catabolite repression. In the present study we examined the physiological effects of glutamate auxotrophy on cellular metabolism and on the nitrogen catabolite repression of asparaginase II. Glutamate auxotrophic cells, incubated without a glutamate supplement, had a diminished internal pool of alpha-ketoglutarate and a concomitant inability to equilibrate ammonium ion with alpha-amino nitrogen. In the glutamate auxotroph, asparaginase II biosynthesis exhibited a decreased sensitivity to nitrogen catabolite repression by ammonium ion but normal sensitivity to nitrogen catabolite repression by all amino acids tested.